Navigating trade-offs on conservation: the use of participatory mapping in maritime spatial planning - Helena Calado; Débora Gutierrez; Albane De Bruyn (npj Ocean Sustainability)
Abstract Maritime spatial planning (MSP) has evolved to incorporate features like authoritative, participatory, ecosystem-based, integrated, future-oriented, and adaptive approaches. MSP seeks a balance between maritime activities and sustainable development within ecological limits, an ecosystem-based approach (EBA). A trade-off in the context of MSP refers to the compromise or exchange between different objectives, interests, or uses of marine resources and space. The aim of this paper is to provide methodological guidelines for applying a trade-off methodology for marine protected areas (MPAs) design within the MSP context. The guidelines have developed participatory-based trade-off scenarios to weigh the impacts of the multi-objective spatial and strategic management measures, using participatory mapping, providing a valuable framework for design of MSP and MPAs. The lessons learned and recommendations provided aim to guide future MSP endeavours, emphasising the importance of continuous improvement, innovation, and adaptation in the dynamic field of MSP for sustainable marine management and conservation.